Applying gamification in student coaching industry : A competitive environment analysis - Tiuraniemi, Aleksi (My University, 2021)
The purpose of this study is to explore if gamification can create competitive advantage in student coaching industry in Finland. Using “game-like” elements in services can engage and motivate customers, which leads to several other positive behavioral patterns. Lately, this phenomenon has attracted the attention of both academia and practice. The aim of this thesis is to explore gamification and its benefits in the context of student coaching in Finland and more specifically the high school students in Finland. To give a foundation for this study and to gain better understanding of the context a competitive environment analysis is conducted of the student coaching industry in Finland. Current state of the industry is analyzed, and different strategic groups are recognized. This analysis takes the perspective of how attractive the market is. The empirical part of the study was conducted by interviewing experts in the student coaching industry in Finland. The data was collected through semi-structured interviews from professionals in the industry, who worked in different companies, which provided different viewpoints on the object of this study. I combined the data from the interviews with secondary data found online and analyzed them together. The findings indicate that using gamification and executing it correctly in educational context it can create positive behavioral patterns in students and further competitive advantage in the market. When gamification is implemented the right way, it has the potential to improve educational experiences, increasing user engagement, activity, social interaction, and other positive behavioral patterns.
Keywords: gamification; coaching; students; industry; motivation (mental objects); fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development